2008
DOI: 10.1038/ijo.2008.258
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity reduces the influence of genetic effects on BMI and waist circumference: a study in young adult twins

Abstract: Objective: Both obesity and exercise behavior are influenced by genetic and environmental factors. However, whether obesity and physical inactivity share the same genetic vs environmental etiology has rarely been studied. We therefore analyzed these complex relationships, and also examined whether physical activity modifies the degree of genetic influence on body mass index (BMI) and waist circumference (WC). Methods: The FinnTwin16 Study is a population-based, longitudinal study of five consecutive birth coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
122
2
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(144 citation statements)
references
References 37 publications
9
122
2
11
Order By: Relevance
“…This is lower than the 78 % observed earlier by Joosen et al , but is congruent with the 55 % observed in a twin study with subjective (Mustelin et al 2009) measures of physical activity, but higher than the 37 % of the twin study with objective measurements (den Hoed et al 2013). In concordance with earlier studies, the present study suggests that the residual variance (43 %) is likely accounted for by unique environmental factors (AE model) (Cai et al 2006;Joosen et al 2005;Mustelin et al 2009;den Hoed et al 2013). However, a role for common environmental factors (ACE model) cannot be excluded, as approximately 262 twin pairs are required to detect such an effect with an additive genetic effect of 60 %, a confidence level of 0.05 and a power of 80 % (Visscher et al 2008).…”
Section: Discussionsupporting
confidence: 80%
“…This is lower than the 78 % observed earlier by Joosen et al , but is congruent with the 55 % observed in a twin study with subjective (Mustelin et al 2009) measures of physical activity, but higher than the 37 % of the twin study with objective measurements (den Hoed et al 2013). In concordance with earlier studies, the present study suggests that the residual variance (43 %) is likely accounted for by unique environmental factors (AE model) (Cai et al 2006;Joosen et al 2005;Mustelin et al 2009;den Hoed et al 2013). However, a role for common environmental factors (ACE model) cannot be excluded, as approximately 262 twin pairs are required to detect such an effect with an additive genetic effect of 60 %, a confidence level of 0.05 and a power of 80 % (Visscher et al 2008).…”
Section: Discussionsupporting
confidence: 80%
“…41,42 Similarly, shared environmental effects are found on childhood physical activity and exercise patterns, 43 but weaken during adolescence 44 and are virtually absent in young adulthood. 45 The effect of childhood home environment thus seems to diminish when children become older and become more independent to make their own choices.…”
Section: Discussionmentioning
confidence: 99%
“…6 A recent Finnish twin study found that physical activity reduces genetic variance of BMI and waist circumference in early adulthood. 45 This suggests that the function of genes predisposing to obesity is suppressed in physically active persons. There is also evidence suggesting a modifying effect of physical activity on specific genes; a Danish study found that the rs9939609 polymorphism of the FTO gene is associated with greater BMI in sedentary persons than in physically active persons.…”
Section: Possible Sources Of Bias In Adoption Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study of Finnish twins the correlation between self-reported and measured BMI was very high [25].…”
Section: Methodsmentioning
confidence: 96%